Effect of grinding with diamond-disc and -bur on the mechanical behavior of a Y-TZP ceramic - Pereira, G. K. R.; Amaral, Marina [UNESP]; Simoneti, R.; Rocha, G. C.; Cesar, P. F.; Valandro, L. F. (Elsevier B.V., 2014)
This study compared the effects of grinding on the surface micromorphology, phase transformation (t -> m), biaxial flexural strength and structural reliability (Weibull analysis) of a Y-TZP (Lava) ceramic using diamond-discs and -burs. 170 discs (15 x 1.2 mm) were produced and divided into 5 groups: without treatment (Ctrl, as-sintered), and ground with 4 different systems: extra-fine (25 mu m, Xfine) and coarse diamond-bur (181 mu m, Coarse), 600-grit (25 mu m, D600) and 120-grit diamond-disc (160 mu m, D120). Grinding with burs was performed using a contra-angle handpiece (T2-Revo R170, Sirona), while for discs (Allied) a Polishing Machine (Ecomet, Buehler) was employed, both under water-cooling. Micromorphological analysis showed distinct patterns generated by grinding with discs and burs, independent of grit size. There was no statistical difference for characteristic strength values (MPa) between smaller grit sizes (D600 - 1050.08 and Xfine - 1171.33), although they presented higher values compared to Ctrl (917.58). For bigger grit sizes, a significant difference was observed (Coarse - 1136.32>D120-727.47). Weibull Modules were statistically similar between the tested groups. Within the limits of this study, from a micromorphological point-of-view, the treatments performed did not generate similar effects, so from a methodological point-of-view, diamond-discs should not be employed to simulate clinical abrasion performed with diamond-burs on Y-TZP ceramics. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Grinding; Zirconium oxide partially stabilized by yttrium; Mechanical properties